(3GdJLGQI GdNGQLjI (B/s - (3GdLed, LeGd LhjOGfs ((3YeGf(B: s (3eQcR GdcJGH GdCcGOjej(B, s, 2013)
(3GdJLGQI GdNGQLjI(B- (3fXQjGJ GdJLGQI GdNGQLjI(B- (3GdCSGdjH GdfXQjI aj GdJLGQI GdNGQLjI(B- (3GdSjGSGJ GdJLGQjI GdNGQLjI(B- (3GdSjGSI GdJLGQjI aj MGdI GdOhdI GdcHjQI heXGgQ aTd GdShb(B- (3eRGjG hYjhH GdMeGjI GdJLGQjI(B- (3GdEJaGbjI GdYGeI ddJLGQI hGdJYQaI GdLeQcjI(B( (3GdLGJ(B)- (3GdJLGQI GdNGQLjI aj GdCQOfs
Keywords: (3GdJLGQI GdNGQLjIs; (3GdJLGQI GdNGQLjI(B- (3GdCQOfs